The Effect of Institutional Ownership, Independent Board, Managerial Ownership, and Liquidity on Firm Value in Basic & Chemical and Food & Beverage Industries - Lenny Widiawati; Rilla Gantino (LJPI UI Bunga Bangsa Cirebon, 2024)
This study aims to provide an analysis of the extent to which institutional ownership, managerial ownership, independent board of commissioners, and liquidity affect firm value in the basic industry & chemicals sector and the food & beverage industry sub-sector listed on the IDX during 2019–2023. The novelty of this research lies in the measurement of institutional ownership through institutional share percentage, independent board through the number of independent commissioners, managerial ownership through managerial shareholding, and liquidity proxied by the current ratio, while comparing two different industry types. The methods used are purposive sampling with secondary data sourced from audited annual reports published on the IDX website. The results show that individually, institutional ownership, independent board of commissioners, and managerial ownership do not significantly affect firm value in both sectors, while liquidity negatively affects firm value only in the basic industry & chemicals sector; however, simultaneously, all variables significantly influence firm value. The conclusion states that although individually the factors are not influential (except liquidity in one sector), together they significantly affect the firm's value, with a higher explanatory power in the basic industry & chemicals sector compared to the food & beverage sector.